Analysis of 213 currently used rehabilitation protocols in foot and ankle fractures. (October 2015) - Pfeifer, Christian G.; Grechenig, Stephan; Frankewycz, Borys; Ernstberger, Antonio; Nerlich, Michael; Krutsch, Werner
Abstract: Introduction: Fractures of the ankle, hind- and midfoot are amongst the five most common fractures. Besides initial operative or non-operative treatment, rehabilitation of the patients plays a crucial role for fracture union and long term functional outcome. Limited evidence is available with regard to what a rehabilitation regimen should include and what guidelines should be in place for the initial clinical course of these patients. This study therefore investigated the current rehabilitation concepts after fractures of the ankle, hind- and midfoot. Methods: Written rehabilitation protocols provided by orthopedic and trauma surgery institutions in terms of recommendations for weight bearing, range of motion (ROM), physiotherapy and choice of orthosis were screened and analysed. All protocols for lateral ankle fractures type AO 44A1, AO 44B1 and AO 44C1, for calcaneal fractures and fractures of the metatarsal as well as other not specific were included. Descriptive analysis was carried out and statistical analysis applied where appropriate. Results: 209 rehabilitation protocols for ankle fractures type AO 44B1 and AO 44C1, 98 for AO 44A1, 193 for metatarsal fractures, 142 for calcaneal fractures, 107 for 5 th metatarsal base fractures and 70 for 5 th metatarsal Jones fractures were evaluated. The mean time recommended for orthosis treatment was 6.04 (SD 0.04) weeks. While the majority of protocols showed a trend towards increased weight bearing and increased ROM over time, the best consensus was noted for weight bearing recommendations. Conclusion: Our study shows that there exists a huge variability in rehabilitation of fractures of the ankle-, hind- and midfoot. This may be contributed to a lack of consensus (e.g. missing publication of guidelines), individualized patient care (e.g. in fragility fractures) or lack of specialization. This study might serve as basis for prospective randomized controlled trials in order to optimize rehabilitation for these common fractures.